2013
DOI: 10.1002/smll.201200672
|View full text |Cite
|
Sign up to set email alerts
|

Transport Phenomena and Conduction Mechanism of Individual Cross‐Junction SnO2 Nanobelts

Abstract: Electrical characteristics of individual cross‐junction nanodevices consisting of two SnO2 nanobelts are systematically investigated. The source–drain current along one nanobelt under constant source–drain voltage is not linearly varied with the ‘gate’ voltage applied on the terminal of the other one. The absolute increments for the source–drain and ‘gate’ current gradually increase as the gate voltage deviates from 0 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…4 It has been reported that a downward bending of 0.1 eV could be observed for water adsorption on stoichiometric SnO 2 (110) surfaces. 24,25 Electron transfer through junction barriers is the dominant mechanism during electron transport within the nanowire network 3,15 (due to the high electron mobility in individual nanowire, the conducting path within a nanowire can be treated as a "short circuit" between the barriers at the nanojunctions) and reduction of the energy barrier will result in a signicant increase of the amount of free carriers owing within the nanonet. Thus the exposure of the nanowire network devices to the humid air results in a reduced electron injection barrier at the nanowire junctions, resulting in a highly conducting pathway.…”
Section: Resultsmentioning
confidence: 99%
“…4 It has been reported that a downward bending of 0.1 eV could be observed for water adsorption on stoichiometric SnO 2 (110) surfaces. 24,25 Electron transfer through junction barriers is the dominant mechanism during electron transport within the nanowire network 3,15 (due to the high electron mobility in individual nanowire, the conducting path within a nanowire can be treated as a "short circuit" between the barriers at the nanojunctions) and reduction of the energy barrier will result in a signicant increase of the amount of free carriers owing within the nanonet. Thus the exposure of the nanowire network devices to the humid air results in a reduced electron injection barrier at the nanowire junctions, resulting in a highly conducting pathway.…”
Section: Resultsmentioning
confidence: 99%
“…For copper selenide, its reported nanostructures are dominated by nanocrystals, nanowires, nanoflakes, and so forth. To the best of our investigation, their belt-/ribbonlike nanostructures with a rectangular cross section have not been involved until now. Concerning copper oxide, its belt-/ribbonlike nanostructures have been only demonstrated in a few reports. However, its porous nanobelts have been rarely developed to fabricate nanosensors. , In fact, beltlike nanomaterials, first reported by Wang et al, have aroused great interest because of their promising building-block function for nanoelectronics, optoelectronics, and nanosensors. Beltlike nanomaterials being endowed with porous structure, their intrinsic characteristics especially for gas-sensing performances are further enhanced, which is attributed to higher active surface-to-volume ratios and more channels for gas diffusion in contrast to solid nanobelts. , Accordingly, development of new synthetic strategies of porous copper selenide and copper oxide nanobelts will not only enrich current copper-based nanostructures, but also further widen their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large active surface area, nanostructured semiconductor metal oxides have been received great attention in many fields, especially for gas sensors. Over the past several decades, considerable efforts have been devoted to preparing their various nanostructures, such as nanoparticles, nanowires, nanorods, nanobelts and nanotubes, and so forth. By employing these nanostructures as sensing units, indeed their gas-sensing performances have been greatly enhanced in contrast to the bulk structures. However, not all nanostructures can effectively contribute to the gas-sensing response among the sensing films composed of them.…”
mentioning
confidence: 99%